Pengaruh Fluktuasi Harga Pangan dan Kontribusinya terhadap Perubahan Inflasi di Kota Medan Sumatera Utara - Rahmi Nofitasari; Herlyna Novasari Siahaan; Indah Kartika Sandra; Tepti Natgar Br Aritonang (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Inflation is highly detrimental to a country's economy. Inflation can be described as the purchasing power of an exchange rate over a period. Rising food prices can contribute to a country's inflation. The decline in a country's currency's purchasing power will impact the decline in people's purchasing power for daily needs. The purpose of this study was to analyze the relationship between price fluctuations and inflation in Medan City. This study primarily relies on secondary data as its primary source of reference. Secondary data was obtained from the website of the Strategic Food Price Information Center (PIHPS) of North Sumatra Province and the Central Statistics Agency (BPS) of North Sumatra Province. The secondary data used in this study are strategic food price data on rice commodities, fresh chicken meat, beef, chicken eggs, shallots, garlic, curly red chilies, green cayenne pepper, cooking oil, and granulated sugar. Additionally, this study utilizes inflation data from Medan City. Price and inflation data were collected monthly from January 2020 to December 2023, encompassing both the pandemic and the post-COVID-19 period. Quantitative analysis uses an econometric model, namely OLS, which can be formulated using multiple linear regression analysis. Based on the test results, several commodities have an impact on inflation in Medan City, including rice, broiler chicken, beef, shallots, cooking oil, and sugar.